Pengaruh Konsentrasi Resin dan Suhu Pemanas Awetan pada Penyempurnaan Lipatan Permanen Kain Poliester 100% - Feny Nur Herawati (Sainteks: Jurnal Sain dan Teknik, 2021)
Permanent press by using resin will increase the resistance of the desired material properties. The refinement process to obtain permanent fold properties in polyester fibers is obtained by forming a polymer resin layer on the surface of the fabric. The more resin used, the less the ability of the fabric to come back from the crease, so the permanent crease finish will be more permanent. However, with more and more resin polymerizing on the surface, the fabric will be stiffer and can reduce the tensile strength of the fiber, the occurrence of the resin polymerization process is influenced by the temperature of the preserved heating when the temperature is less then the resin is not formed perfectly or if the temperature is too high it can cause damage to the fiber. This test was carried out on 100% polyester fabric with variations in the concentration of melamine formaldehyde resin 40 g/l, 50 g/l, 60 g/l, 70 g/l and variations in the curing temperature of 1600C, 1700C, 1800C, 1900C. Tests carried out include re-testing of the folds and tensile strength of the fabric. The results showed that the optimum conditions achieved in this experiment were at a concentration of melamine formaldehyde resin of 60 g/l with a preserved heating temperature of 1700C, a low folding angle value of 740 was obtained with a tensile strength value that above the minimal standards, namely the warp 75.7 Kg and weft 22.7 Kg.